Chromatographic determination and toxicological potential evaluation of selected micropollutants in aquatic environment—analytical problems. Issue 3 (14th January 2016) - Bohdziewicz, Jolanta; Dudziak, Mariusz; Kamińska, Gabriela; Kudlek, Edyta
Abstract: In this study, the analytical procedures for the improved extraction and determination of the selected micropollutants (anthracene, pentachlorophenol, octylphenol, benzo(a)pyrene, and diclofenac) in aqueous environment are proposed. These methods were based on application of gas chromatography coupled with mass spectrometry and solid phase extraction for isolation of tested analytes from water samples. Compared to standard procedures currently used in the range presented in this paper, the authors' modifications of analytical procedures allowed increasing the recovery rate of analytes. Within modification of procedures, hyamine, methanol were used. The substances increase solubility of analytes in water, for instance. Toxicological potential of samples containing tested micropollutants in different environmental matrix was evaluated. Proposed analytical procedures allow the quantitative determination of five different compounds in aquatic environment with satisfactory repeatability and precision of measurements. Applied modifications of analytical procedures had an influence on the increase of recovery degree of compounds. Extraction of micropollutants from effluent exceeded 60% and depended on compounds concentration in the samples, excluding the determination for lower concentration of anthracene. The limits of quantitation LOQ (in ng/L) were as follows: 6.5 for anthracene and octylphenol, 8.5 for diclofenac, and 10 for pentachlorophenol and benzo(a)pyrene. It was found that Microtox ® assay allows the quick evaluation of toxicological potential of selected micropollutants. The toxicological potential (expressed as EC50, in mg/L) of deionized water samples containing micropollutants was equal to: 12.8; 2.2; 1.4; 6.6; 23.1 for anthracene, pentachlorophenol, octylphenol, benzo(a)pyrene, and diclofenac, respectively. However, the toxicity was also dependent on environmental matrix. The explanation of this phenomenon requires further research.